The ability of terrestrial Oligochaeta to survive in ultramafic soils and the assessment of toxicity at different levels of organisation - Maleri, Rudolf A. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Botany and Zoology)) -- University of Stellenbosch, 2006.